Gene therapy in the treatment of congenital hearing loss (Research, Society and Development, 2025)
Introduction: Congenital hearing loss can be classified as conductive or sensorineural, ranging from unilateral to bilateral, mild to profound, and stable or progressive. Among its causes, those of genetic origin represent approximately 60% of cases. This condition can significantly impact cognitive development, making early screening and intervention essential.The objective of this article is to present gene therapy possibilities for the future treatment of hereditary hearing loss through a narrative literature review. Methodology: This is an integrative literature review, based on articles published in Portuguese and English in the Lilacs, Medline and Scielo databases. Results: Gene therapy has emerged as an innovative strategy for the treatment of hereditary hearing loss (HHL), especially in mutations in the GJB2, SLC26A4 and MYO7A genes. However, challenges such as the anatomical complexity of the cochlea and the genetic heterogeneity of the inner ear still hinder its clinical implementation. Conclusion: Despite its innovative potential, gene therapy for congenital hearing loss still requires additional studies to ensure its efficacy and safety before being consolidated as a viable therapeutic option.